Peningkatan Mutu Pendidikan, Ekonomi dan Status Sosial Anak Yatim Melalui Bantuan Yayasan Ash-shilah (studi Analisis Terhadap Keberadaan Anak Yatim di Kota Medan) - Kamalia Kamalia (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2024)
Orphans are a social group that is vulnerable to disruption in their education, economic pressure on their families, and social marginalization due to the loss of parental support. Within the framework of Islamic social responsibility, philanthropic institutions have a strategic role in addressing these issues in a sustainable manner. This study aims to analyze the role of the Ash-Shilah Foundation in improving the quality of education, economic conditions, and social status of orphans in the city of Medan. The study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation involving foundation managers, guardians, and beneficiaries. The results show that integrated assistance programs covering sustainable educational support, productive economic empowerment, and social guidance contribute positively to the sustainability of education, family economic resilience, and increased social acceptance of orphans in the community. The effectiveness of the program is supported by institutional governance, international donor networks, and systematic monitoring mechanisms. These findings confirm that Islamic philanthropy will have a greater impact if it is carried out through a long-term empowerment model, encouraging readers to reflect on the role of philanthropy as an instrument of sustainable human development.